The Study of Pyridazine Compounds on Prostanoids: Inhibitors of COX, cAMP Phosphodiesterase, and TXA2 Synthase - Mohammad Asif (Journal of Chemistry)
The pyridazine moiety is an important structural feature of various pharmacological active compounds. Synthetic pyridazine compounds have been reported as effective antiprostaglandins (PGs), 5-lipoxygenase (5-LOX), and antiplatelet agents, that is, inhibitors of prostaglandin or cyclooxygenase (COX-I & COX-II) enzyme, platelet cAMP phosphodiesterase, and thromboxane A2 (TXA2) synthase. These compounds are selective and nonselective COX inhibitors and showed analgesic, anti-inflammatory, and antipyretic activity. Pyridazine compounds with antiplatelet agents inhibited TXA2 enzyme. Pyridazines also exhibited antirheumatoid activity. These pyridazine compounds hold considerable interest relative to the preparation of organic intermediates and other anticipated biologically active compounds.